Dengue associated hemophagocytic syndrome: a case report - Nessa, Azimun; Haque, Hasna Fahmima; Ahmed, AKM Shaheen (BIRDEM Medical Journal, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is an aggressive and life-threatening syndrome of excessive immune activation. Several conditions are responsible for triggering HLH in clinically stable patients who respond to treatment of the underlying condition alone. These conditions include infection, rheumatological diseases and lymphoid malignancies. We are discussing a case of HLH who presented at age of 22 years that was triggered by dengue virus infection. Patient presented with an acute febrile illness and was diagnosed with dengue hemorrhagic fever. Despite appropriate supportive therapy, he had clinical deterioration. Evaluation revealed features of HLH. He was successfully treated with glucocorticoids and had an uneventful recovery. This case adds to the limited adult cases of virus-associated hemophagocytic syndrome in the literature and emphasizes the need for prompt recognition and treatment of this rare complication. BIRDEM Med J 2023; 13(1): 49-51